Cardiovascular Implications of the COVID-19 Pandemic: A Global Perspective - Boukhris, Marouane (Can J Cardiol, 2020)
The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), represents the pandemic of the century, with approximately 3.5 million cases and 250,000 deaths worldwide as of May 2020. Although respiratory symptoms usually dominate the clinical presentation, COVID-19 is now known to also have potentially serious cardiovascular consequences, including myocardial injury, myocarditis, acute coronary syndromes, pulmonary embolism, stroke, arrhythmias, heart failure, and cardiogenic shock. The cardiac manifestations of COVID-19 might be related to the adrenergic drive, systemic inflammatory milieu and cytokine-release syndrome caused by SARS-CoV-2, direct viral infection of myocardial and endothelial cells, hypoxia due to respiratory failure, electrolytic imbalances, fluid overload, and side effects of certain COVID-19 medications. COVID-19 has profoundly reshaped usual care of both ambulatory and acute cardiac patients, by leading to the cancellation of elective procedures and by reducing the efficiency of existing pathways of urgent care, respectively. Decreased use of health care services for acute conditions by non-COVID-19 patients has also been reported and attributed to concerns about acquiring in-hospital infection. Innovative approaches that leverage modern technologies to tackle the COVID-19 pandemic have been introduced, which include telemedicine, dissemination of educational material over social media, smartphone apps for case tracking, and artificial intelligence for pandemic modelling, among others. This article provides a comprehensive overview of the pathophysiology and cardiovascular implications of COVID-19, its impact on existing pathways of care, the role of modern technologies to tackle the pandemic, and a proposal of novel management algorithms for the most common acute cardiac conditions.